2006
DOI: 10.1111/j.1365-2516.2006.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with treatment and understanding of own disease in patients with severe and moderate haemophilia

Abstract: It is well known that teenagers with chronic diseases have problems complying with their treatment. The aim of this study was to evaluate the patient's knowledge of haemophilia and his compliance to prophylactic treatment, and the age at which the patient took over the responsibility for his disease and to create educational material for teenagers and adolescents. This was a prospective multicentre study performed in Hemophilia Treatment Centres in Scandinavia. A total of 108 of 134 patients, between 13 and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
164
5
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(179 citation statements)
references
References 4 publications
9
164
5
1
Order By: Relevance
“…Studies of young people and adults with haemophilia have shown that 69% of patients aged 13-25 years [21] and 96% of patients aged over 25 [22] were aware of heredity i.e. a healthy son and carrier daughter.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of young people and adults with haemophilia have shown that 69% of patients aged 13-25 years [21] and 96% of patients aged over 25 [22] were aware of heredity i.e. a healthy son and carrier daughter.…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to better understanding of their illness as well as the necessity for factor infusions and supportive measures when bleeding occurs. A study of 108 hemophiliacs done by Lindvall et al showed that patients started to become responsible for his illness in terms of treatment at a mean age of 14.1 years, showing their deep of understanding of the disease process [16].…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia is often associated with a stigma, and the behavior of the immediate social environment of a child (family and peers) can be negatively affected by the knowledge of the child's health condition. Parents might behave in an overprotective way, 12 and teachers might not allow a child to participate in a certain school event involving physical activity. 13 The ICF and ICF-CY The classification of health has undergone major developments in the last decades.…”
Section: Health-related Quality-of-lifementioning
confidence: 99%